Dynamic Business Plan for a High-Performance Feed Pelleting Project in Sikasso, Mali - Idoudi, Zied; Rudiger, Udo; sow, ahmadou (International Center for Agricultural Research in the Dry Areas, 2024)
Feed is a fundamental component of small ruminant value chains and has a significant impact on animal growth, health, productivity and overall profitability. In Mali, the need for efficient feed processing and effective marketing strategies is critical to ensure a consistent supply of high-quality feed from locally available resources. The small ruminant sector plays an important role in rural economies, particularly for women who often depend on these animals for their livelihoods. In 2024, the CGIAR research initiative known as SAPLING launched two innovative feed processing units in Mali – in Farakala (Sikasso) and Baroueli (Segou). These state-of-the-art units were co-designed and locally produced to strengthen farmer organisations and establish multi stakeholder innovation platforms (MSIPs). The aim is to facilitate the production and sale of animal feed using local ingredients such as cotton cake and residues from cereal and legume crops. Each unit has advanced machinery, including grinders, conveyors, feed mixers and pelletizers, with a production capacity of 500 kg of feed pellets per hour. The allocation of these feed production units targets two dynamic communities: the Wutango Women Farmers Group in Sikasso and the Baroueli Pastoralist Women's Association. To promote sustainable operations and business growth, both communities participated in joint workshops and field visits to develop tailor-made business plans. This Business plan covers key aspects such as management, marketing strategies, input supply channels, potential profitability and financial mechanisms for the Wutango Women Farmers Group in Sikasso.